Pengaruh Kompensasi, Kepemimpinan, dan Lingkungan Kerja Fisik Terhadap Kepuasan Kerja Karyawan Hotel Taman Harum Ubud Gianyar - Rumada, Gede; Utama, I Wayan Mudiartha (E-Jurnal Manajemen, 2013)
Job satisfaction is a positive feeling about one's job that result of an evaluation of its characteristics. Job satisfaction refers to the individual's attitude in general toward his work. In order to employees have a sense of job satisfaction, an organization needs to consider factors that influences such as compensation, leadership, and physical work environment. The purpose of the study was to find out the effect of compensation, leadership, and physical work environment variable toward employee job satisfaction at Hotel Taman Harum Ubud, Gianyar, by number of sample were 54 respondents. Variable  of compensation, leadership, and physical work environment simultaneously or partially have significant effect towards employee job satisfaction at Hotel Taman Harum Ubud, Gianyar. Keywords: Compensation, Leadership, Job Environment, Job Satisfaction